Efforts to Improve Student Learning Outcomes Using Project Based Learning in Mathematics Learning - Solehah; Widyaningsih; Siti Sarah; Wahyu Purwasih (Jurnal Sekolah Dasar, 2023)
This research was conducted with the aim of knowing efforts to improve students' learning outcomes using the Project Based Learning model in Mathematics class 3B at MI Darul Hikmah Bantarsoka. This research is a class action research based on the theory of Kemmis and Taggar. The subjects in this study were class 3B MI Darul Hikmah Bantarsoka Purwokerto students totaling 28 students. Data collection techniques in this study used observation, interviews, documentation and learning outcomes tests. The research data were analyzed with qualitative descriptive techniques to analyze the observation results and quantitative descriptive to analyze the test results. The results of the study show that learning the Project Based Learning model can improve the ability of student learning outcomes in mathematics learning. This can be seen from the actions of Cycle I students who achieved an average score in Cycle I of 38.07 and in Cycle II of 73.2. Meanwhile, the number of students who reached KKM in the first cycle was 18.5% and cycle II was 66.7%.